Effect, Mechanism, and Applications of Coding/Non-coding RNA m6A Modification in Tumor Microenvironment - Si, Chaohua; Chen, Chen; Guo, Yaxin; Kang, Qiaozhen; Sun, Zhenqiang (Frontiers in Cell and Developmental Biology, 2021)
Abstract: Tumor Microenvironment (TME) is the site of tumor cell growth and metastasis which plays an important role in the occurrence and development of tumors. TME includes immune cells, fibroblasts, lymphocytes, and other components, at the same time, a variety of chemical modifications that affect the progression of cancer also occur in the TME. Among them, the N6-methyladenosine RNA modification (m6A RNA modification) is the most abundant internal modification existing in coding and non-coding RNA, which has a great effect on the cancer process and can be used as a biomarker and potential therapeutic target for tumor therapy. In this review, we summarize the role of m6A RNA modification in TME, as well as its potential applications in cancer therapy. Anyway, an in-depth understanding of the relationship between TME and m6A RNA modification will provide new approaches and ideas for future cancer treatment.